Deviations of Sovereignty, or the anti-modern Outlook on Westphalia (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
To the extent that the Peace of Westphalia is the concretion of the modern concept of sovereignty and international order, these treaties provide a precise reference to anti-modern thinking on sovereignty and the state. One consequence of the Napoleonic era was the ruin of the Westphalian system of balances, the restoration is used to evaluate whether that solution was the source of contemporary evils or the best barrier.